Local level politics in Bangladesh: Organization and process - Wohab, Md. Abdul; Akhter, Sanzida (BRAC University, 2010)
This paper focuses on local level politics and the organization of political parties to examine how the political leaders mobilize their supporters at the local level. The involvement of local people is also analyzed here. Moreover, some aspects of political awareness from within and outside the party are covered in the paper. Here, how local level politics are important in our political arena and what sort of cohesion exists between local level politics and national level politics also focused. To what extent and under what conditions do the political leader in local area, the relation between local and national politics and their contribution to development activities are also focused.